LATIHAN SQUAT DENGAN PROGRESSIVE RESISTANCE EXERCISE (PRE) UNTUK PENDERITA OSTEOARTHRITIS (OA) - Anjari Dyah K., Warih (Jurnal Farmasi (Journal of Pharmacy), 2017)
Osteoarthritis sufferers have a typical joint pain that is pain that increases weight when sustaining body weight or during activity, stiffness in the morning and feeling sore when the old joints are rested. On physical examination found tenderness, crepitations with or without restricted joint motion. Patients with lower extremity osteoarthritis may experience limitations in daily activities such as walking, bathing, dressing, using toilets, and doing household chores. Quadriceps muscle weakness is a common condition in patients with knee osteoarthritis which leads to disused atrophy due to the lack of use of the muscle on the sick side of the knee. The purpose of this study to determine the effect of both exercises on Osteoarthritis patients. The methodology used in this research is Pre and Post Test with Control Group Design. The results showed that the value of significance in both the squat exercise and progressive resistance exercise groups on the increase of functional activity in knee OA were all p <0.05 indicating that Close kinetic chain (p = 0.00) and Progressive Resistance Exercise (p = 0.001) similarly affects the increased functional activity in knee osteoarthritis. There is a difference in the effect of Squat exercise with progressive resistance exercise in improving functional activity in patients with knee osteoarthritis